The Eight and a Half Year Journey of Undiagnosed AD: Gene Sequencing and Funding of Advanced Genetic Testing Has Led to Hope and New Beginnings - Gozes, Illana; Patterson, Marc C.; Van Dijck, Anke; Kooy, R. Frank; Peeden, Joseph N.; Eichenberger, Jacob A.; Zawacki-Downing, Angela; Bedrosian-Sermone, Sandra (Frontiers in Endocrinology, 2017)
Background Activity-dependent neuroprotective protein (ADNP) is one of the most prevalent de novo mutated genes in syndromic autism spectrum disorders, driving a general interest in the gene and the syndrome. Aim The aim of this study was to provide a detailed developmental case study of ADNP p.Tyr719* mutation toward improvements in (1) diagnostic procedures, (2) phenotypic scope, and (3) interventions. Methods Longitudinal clinical and parental reports. Results AD (currently 11-year-old) had several rare congenital anomalies including imperforate anus that was surgically repaired at 2 days of age. Her findings were craniofacial asymmetries, global developmental delay, autistic behaviors (loss of smile and inability to make eye contact at the age of 15 months), and slow thriving as she gradually matures. Comprehensive diagnostic procedures at 3 years resulted in no definitive diagnosis. With parental persistence, AD began walking at 3.5 years (skipping crawling). At the age of 8.5 years, AD was subjected to whole exome sequencing, compared to the parents and diagnosed as carrying an ADNP p.Tyr719* mutation, a causal recurring mutation in ADNP (currently 17/80 worldwide). Brain magnetic resonance imaging demonstrated mild generalized cerebral volume loss with reduced posterior white matter. AD is non-verbal, communicating with signs and word approximations. She continues to make slow but forward developmental progress, and her case teaches newly diagnosed children within the ADNP Kids Research Foundation. Conclusion This case study emphasizes the importance of diagnosis and describes, for the first time, early motor intervention therapies. Detailed developmental profile of selected cases leads to better treatments.